SARS-CoV-2 seroprevalence and associated factors among outpatient attendees at health facilities in different provinces in Chad - Koutaya Dezoumbe; Oumaima Djarma; Andrillene Laure Deutou Wondeu; Fatima Abdelrazak Zakaria; Sabrina Atturo; Nathan Naïbeï; Franck J. D. Mennechet; Denise Campagna; Abdoulaye Boukar; Choroma Ahmat Moussa; Issa Mahamat; Nontegyol Armand; et al. (BMC Infectious Diseases, 2024)
Abstract Background Chad with 7,698 confirmed cases of infection and 194 deaths since the beginning of the COVID-19 pandemic, is one of the African countries with the lowest reported case numbers. However, this figure likely underestimates the true spread of the virus due to the low rate of diagnosis. The high rate of asymptomatic infections reflects the reality of SARS-CoV-2 transmission in Chad. In this study, we estimated the seroprevalence and identified factors associated with SARS-CoV-2 infection. Methods A cross-sectional study was conducted between September 2022 and February 2023. A total of 1,290 plasma samples were collected from outpatient attendees at Health Facilities located in 11 provinces of Chad and tested by ELISA method, for the presence of IgG antibodies to SARS-CoV2 nucleocapsid (N) protein. KoboToolbox was used to gather data from the participants and data were analyzed using STATA 16. Results The overall seroprevalence was 83.0% [95% CI = 81.6%—85.5%], with variations between provinces, ranging from 99.2% [95% CI = 94.0%—100%] in Moundou (Southern Chad) to 46.8% [95% CI = 36.0% -57.1%] in Biltine (Eastern Chad). Factors associated with the seroprevalence included military occupation (OR = 0.37 CI [0.80–1.77] p = 0.025) and age group between 55–64 years (OR = 0.33 CI [0.15–0.72] p = 0.005). While, other factors, such as gender and age were not significantly associated with seroprevalence. Conclusion Our results indicated that, the seroprevalence of COVID-19 in Chad is among the highest in Sub-Saharan Africa. These estimates could guide the response and public health policy decisions, enhancing the management of future outbreaks involving respiratory pathogens.